The Future of Work in a Sustainable Digital Economy : Human Capital, Automation, and Equity (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
A sustainable digital economy is an economic system that integrates digital technology, social sustainability, and resource efficiency within production processes and labor distribution. Advances in information technology, automation, and artificial intelligence have transformed the structure of the global labor market and created skill disparities among workers. The unpreparedness of human resources in facing digital transformation has led to gaps in access to training, technological literacy, and equal employment opportunities. Strengthening human capital is therefore a strategic solution to maintain balance between technological progress and social justice. This study employs a descriptive qualitative approach through Focus Group Discussions and literature reviews within the 2022–2025 period to analyze the interrelationships between competency development, automation implementation, and digital equity. The findings indicate that improving digital capabilities through upskilling, reskilling, and technology-based education enhances workforce resilience against disruption. Collaboration among government, industry, and educational institutions is proven to be effective in expanding training access, reducing the digital divide, and creating an inclusive and adaptive work ecosystem in the era of a sustainable digital economy.